2014
DOI: 10.1371/journal.pone.0112714
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of Apoptosis Signal-Regulating Kinase 1 (ASK1) Protects Pancreatic Beta-Cells from Stress-Induced Death but Not from Glucose Homeostasis Alterations under Pro-Inflammatory Conditions

Abstract: BackgroundType 2 diabetes is characterized by pancreatic beta-cell dysfunction and is associated with low-grade inflammation. Recent observations suggest that apoptosis signal-regulating kinase 1 (ASK1) is involved in beta-cell death in response to different stressors. In this study, we tested whether ASK1 deficiency protects beta-cells from glucolipotoxic conditions and cytokines treatment or from glucose homeostasis alteration induced by endotoxemia.Methodology/Principal FindingsInsulin secretion was neither… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…First, normal diet-fed mice were subjected to a glucose tolerance test (GTT) and an insulin tolerance test (ITT) after an overnight fast or 6 h of fasting, respectively. The results showed that there was no difference in glucose clearance or insulin sensitivity between the two genotypes (S3A-C Figs), which is consistent with a previous study, as evidenced by hyperglycemic clamp and hyperinsulinemic-euglycemic clamp analyses [58]. However, we found that glucose clearance was significantly aggravated in global ASK1KO mice after 10 weeks of HFD exposure (S3D-G Figs).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…First, normal diet-fed mice were subjected to a glucose tolerance test (GTT) and an insulin tolerance test (ITT) after an overnight fast or 6 h of fasting, respectively. The results showed that there was no difference in glucose clearance or insulin sensitivity between the two genotypes (S3A-C Figs), which is consistent with a previous study, as evidenced by hyperglycemic clamp and hyperinsulinemic-euglycemic clamp analyses [58]. However, we found that glucose clearance was significantly aggravated in global ASK1KO mice after 10 weeks of HFD exposure (S3D-G Figs).…”
Section: Resultssupporting
confidence: 91%
“…Nonetheless, we observed a significant increase in fasting glucose levels in global ASK1KO mice (S3E and H Figs), but fasting glucose levels did not seem to be altered in hepatocyte-specific ASK1KO mice [65], suggesting that there are other ASK1-dependent regulatory mechanisms for glucose homeostasis. One possibility is a malfunction in insulin secretion, but this is unlikely given the previous results using the hyperglycemic clamp method [58]; however, impaired insulin secretion in fasted HFD-fed ASK1KO mice is possible.…”
Section: Discussionmentioning
confidence: 99%
“…First, normal diet-fed mice were subjected to a glucose tolerance test (GTT) and an insulin tolerance test (ITT) after an overnight fast or 6 h of fasting, respectively. The results showed that there was no difference in glucose clearance or insulin sensitivity between the two genotypes ( S3A–S3C Fig ), which is consistent with a previous study, as evidenced by hyperglycemic clamp and hyperinsulinemic-euglycemic clamp analyses [ 57 ]. However, we found that glucose clearance was significantly aggravated in global ASK1KO mice after 10 weeks of HFD exposure ( S3D–S3G Fig ).…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, we observed a significant increase in fasting glucose levels in global ASK1KO mice ( S3E and S3H Fig ), but fasting glucose levels did not seem to be altered in hepatocyte-specific ASK1KO mice [ 64 ], suggesting that there are other ASK1-dependent regulatory mechanisms for glucose homeostasis. One possibility is a malfunction in insulin secretion, but this is unlikely given the previous results using the hyperglycemic clamp method [ 57 ]; however, impaired insulin secretion in fasted HFD-fed ASK1KO mice is possible.…”
Section: Discussionmentioning
confidence: 99%
“…Insulin secretion was measured in static conditions at 37°C as previously described [ 19 ]. After a 30 min starvation in DMEM without glucose, insulin secretion was measured during 2 h in HEPES-balanced Krebs-Ringer bicarbonate buffer (125 mM NaCl; 5.9 mM KCl; 1.2 mM MgCl 2 ; 1.3 mM CaCl 2 ; 25 mM HEPES, pH 7.4) containing 0.1% BSA and different glucose concentrations (2.5 mM or 20 mM).…”
Section: Methodsmentioning
confidence: 99%